If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -19 = -61 Reorder the terms: -19 + 6x = -61 Solving -19 + 6x = -61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 6x = -61 + 19 Combine like terms: -19 + 19 = 0 0 + 6x = -61 + 19 6x = -61 + 19 Combine like terms: -61 + 19 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| 2x+2x-4+4x=76 | | -2-(-15)= | | -7t^2-3t+7=0 | | 2(ax+b)+3=x | | -5j^2+2j+5=0 | | 10-1x=20+5x | | 13x+5=50 | | 6y^2-7=0 | | y=-4(x-3) | | y=-4x(x-3)(x+2)(2x-1) | | 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 | | (3c-7)(2c-5)= | | 2m+6n+4m+8n= | | 37-29=4 | | 2x-4=2(5+x) | | -80+360= | | =12+6(8m-3) | | (90)(-4)= | | 4yx^4*2x^2y^5=0 | | 13/9x2/3 | | 4xy*3xy^5*4x^4y^2=0 | | 4m^2*n=0 | | x-.3x=8000 | | x/43=-75-87 | | 3x-5*2=15 |